2023
DOI: 10.1097/mco.0000000000000988
|View full text |Cite
|
Sign up to set email alerts
|

Bone health: biology and nutrition

René Rizzoli,
Thierry Chevalley

Abstract: Purpose of review Recent findings in the influence of dietary patterns, dairy products, beverages and microbiota composition and function on bone health are reviewed and discussed. Recent findings Evidence is accumulating on the increased risk of fracture in individuals following a vegan diet. Meta-analysis of randomized controlled trials indicates a favourable, though of low amplitude, effect of dairy products on bone mass accrual during childhood and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…There are several factors underlying the impact of weight loss on bone health, including clinical, medical, behavioral, nutritional, and genetic variables (i.e., reduced mechanical load, loss of muscle mass, and changes in the secretion of gut hormones and adipokines) [ 5 , 6 ]. Indeed, nutritional aspects, including dietary patterns and strategies are among the modifiable lifestyle factors related to bone health [ 7 , 8 , 9 ]. Some studies showed that people with overweight and obesity have greater bone mineral density (BMD) when compared to individuals with normal weight [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are several factors underlying the impact of weight loss on bone health, including clinical, medical, behavioral, nutritional, and genetic variables (i.e., reduced mechanical load, loss of muscle mass, and changes in the secretion of gut hormones and adipokines) [ 5 , 6 ]. Indeed, nutritional aspects, including dietary patterns and strategies are among the modifiable lifestyle factors related to bone health [ 7 , 8 , 9 ]. Some studies showed that people with overweight and obesity have greater bone mineral density (BMD) when compared to individuals with normal weight [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%